Reevaluation of thyroid nodule surgical treatment. - Tchekmedyian, Vartan; Santana, Carlos; Praderi Gambardella, Luis; Ricciardi, Norma; Garat, Eduardo (Cirugía del Uruguay, 1989)
Authors analyse 581 patients submitted to thyroid surgery, operated on in Surgical Clinic "F" and another extra-hospital population durlng a period of 12 years. They clinically define the thyroid nodule entity (TN) setting it apart from the uninodular goiter. They study TN clinically, with gammagraphy, and cytological puncture.